Interactions Between Child Personality and Parenting in Relation to Child Well-Being: Support for Diathesis–Stress and Differential Susceptibility Patterns - Loginova, Svetlana V.; Slobodskaya, Helena R. (Frontiers in Psychology, 2021)
It is well recognized that children’s individual characteristics moderate the effects of developmental conditions on child well-being. The majority of interactions follow a diathesis–stress pattern, there is also evidence for differential susceptibility and vantage sensitivity models. The present study aimed to examine interactions between parenting and child personality in relation to Russian child well-being and to evaluate the models for moderated relationships. Participants were primary caregivers of 370 children aged 2–7 years. Moderation effects were examined using hierarchical multiple regression and bivariate linear models. In order to differentiate between the models of environmental sensitivity, the analysis of regions of significance was used. Consistent with a diathesis–stress framework, the results revealed that among children low in conscientiousness and high in activity, punitive parenting was a risk factor for externalizing problems; among introverted and fearful children punitive parenting was a risk factor for internalizing problems. Positive parenting/Involvement was a protective factor for internalizing behavior only for children low in openness. The findings also demonstrate an evidence for differential susceptibility model: Children low in Beta higher-order personality trait (also known as Plasticity or Personal Growth) showed more total problems when faced with low positive parenting, but fewer problems when experiencing high-quality parenting.